Information systems supported organizational learning as a competitive advantage - Jose Manuel Arias; Julian Miguel Solana (Journal of Industrial Engineering and Management (JIEM), 2013)
Purpose: The purpose of this paper is to analyze the characteristics that make information systems useful in gathering and processing information with the aim of organizational learning and subsequent structural adaptation for better fitting to market requirements. Design/methodology/approach: Adaptation is a must when turning to foster the competitiveness and sustainability of the organization. Findings and Originality/value: It is clear that information systems can really create a difference in the way an organization acquires information from its environment and from itself in order to achieve a high-quality decision taking process. Research limitations/implications: Organizations have to look inside themselves in order to ensure the comprehension of their core competencies and the way they carry them out. Practical implications: Organizational learning is one of the means employed by organizations to get adapted to their surrounding environment. Social implications: Systems engineering techniques can be applied in order to leverage these core competencies and make organizations adaptable to the organizational environment requirements through the use of information systems. Originality/value: To obtain competitive advantages in the market.
Keywords: 650; competitive advantage; information systems; knowledge management; the learning organization